Tracing the "Islamic Golden Age" to Revitalize the Scientific Paradigm - Kusumawardhana, Gelar Taufiq; Isana, Widiati; Isnendes, Chye Retty; Hidayat, Asep Achmad; Samsudin, Samsudin; Martinez, Rico (International Journal of Language and Culture, 2024)
This research aims to analyze the concept of the Islamic Golden Age abbreviated as IGA, which is agreed upon by Western scholars and Muslim scholars and occurred in the history of Islamic culture and civilization. This research examines the possibility of grounding the characteristics and scientific paradigm of IGA in modern situations through several focuses of study, namely (1) the background of the development of the IGA concept, (2) the stage of development of the IGA concept, (3) the position of scientific activities in the map of cultural constellation (culture) and civilization (civilization) IGA, and (4) the characteristics and scientific paradigm of IGA. These four things are considered to be able to trigger the development stage of scientists, sciences, and inventions. The method used in conducting the research is descriptive-analytic of literature sources. This is done as a mapping of the entire overview of the IGA concept. This research approach is a history approach, both through a diachronic history approach and a synchronic history approach. In addition, it refers to the development of theories obtained deductively through literature studies. The basis of the research is then strengthened by conducting a form of inductive reasoning on the data obtained in this research in order to solve the final conclusions that are based on the data obtained.